Hypoglycaemia is more frequent in type 2 diabetic patients with co-morbid vascular disease: an analysis of the DiaRegis registry - Gitt, Anselm Kai; Deeg, Evelin (European journal of preventive cardiology, 2012)
Background: Patients with type-2 diabetes are at risk for treatment- and disease-related complications. Little is known about the interrelation of hypoglycaemia and co-morbid vascular disease (VD), defined as coronary heart disease, stroke and peripheral arterial disease., Hypothesis: Hypoglycaemia is associated with co-morbid VD in diabetic patients., Methods: DiaRegis is a prospective registry that included patients with type-2 diabetes in 2009/2010. Metric variables are displayed as median and quartiles. For the comparison of patients with or without VD Odds Ratios (OR) were determined from univariate analyses and adjusted for differences in patient characteristics (multivariable analysis)., Results: Data on hypoglycaemia and VD within the last 12 months were available for 3741 patients (98.2%) with a median (IQR) age of 65.9 (57.6-72.9) years; 46.7% were female. VD patients (n = 909; 24.3%) were older (70.7 vs 63.9 years; p < 0.0001), less often female (33.6% vs 50.9%; p < 0.0001) and had had diabetes for a longer duration (6.4 vs 5.4 years; p < 0.0001). Mean cholesterol (total, HDL and LDL) was also slightly lower (p < 0.0001). Glycaemic control (HbA1c, fasting and postprandial glucose) was comparable. VD patients received less metformin (80.7 vs 85.2%; p < 0.01) and more sulfonylureas (31.8 vs 27.6%; p < 0.05). There was an increased incidence of symptomatic hypoglycaemia with or without requiring help and with a need for medical assistance. After adjusting a number of baseline variables the rates of symptomatic hypoglycaemias with help remained significantly increased (OR 3.73 (95% CI 1.31-10.65) in patients with VD., Conclusions: As hypothesized there is a strong association between the incidence of hypoglycaemia and vascular disease at comparable glycaemic control, which confirms prior randomized controlled trial data suggesting an interrelationship between hypoglycaemia and vascular disease.
First published May 31, 2011
Gesehen am 29.06.2018